Causal association between obstructive sleep apnea and gastroesophageal reflux disease: A bidirectional two-sample Mendelian randomization study - Zhu, Qianyin; Hua, Lijiangshan; Chen, Lingshan; Mu, Tingyu; Dong, Die; Xu, Jiayi; Shen, Cuizhen (Frontiers in Genetics, 2023)
Objectives: Correlations between obstructive sleep apnea (OSA) and gastroesophageal reflux disease (GERD) have been detected in previous observational studies. However, this association remains uncertain due to the potential presence of selection and confounding biases. Therefore, this bidirectional two-sample mendelian randomization (MR) study was conducted to evaluate the causal relationship between OSA and GERD. Methods: In this study, instrumental variables (IVs) for OSA were selected from publicly available genetic summary data (27,207 cases and 280,720 controls). Summary statistics for GERD were obtained from a genome-wide association study of 602,604 individuals. The inverse variance weighted (IVW) method was used as the main MR method. The MR-Egger intercept test, MR pleiotropy residual sum and outlier, and leave-one-out analysis were used to detect pleiotropy. Heterogeneity was detected by Cochran’s Q test. Results: The IVW results revealed that OSA [odds ratio (OR): 1.19, 95% confidence interval (CI): 1.11-1.28, p = 8.88E-07] was causally associated with the incidence of GERD. Moreover, there was evidence of GERD leading to OSA in the IVW analysis (OR: 1.44, 95%CI: 1.33-1.57, p = 7.74E-19). No directional pleiotropy was detected by the MR-Egger intercept test (all p > 0.05). Conclusion: This study found that OSA is linked to a higher incidence of GERD, and vice versa. This finding might be helpful for the screening and prevention of these two diseases.